Immunoneutralization of TGFβ1 Improves Skeletal Muscle Regeneration: Effects on Myoblast Differentiation and Glycosaminoglycan Content. (2nd April 2009) - Zimowska, M.; Duchesnay, A.; Dragun, P.; Oberbek, A.; Moraczewski, J.; Martelly, I.
Abstract : When injured by crushing, the repair of the slow-twitch soleus rat muscle, unlike the fast-twitch EDL, is associated with fibrosis. As TGFβ 1, whose activity can be controlled by glycosaminoglycans (GAG), plays a major role in fibrosis, we hypothesized that levels of TGFβ 1 and GAG contents could account for this differential quality of regeneration. Here we show that the regeneration of the soleus was accompanied by elevated and more sustained TGFβ 1 level than in the EDL. Neutralization of TGFβ 1 effects by antibodies to TGFβ 1 or its receptor TGFβ -R1 improved muscle repair, especially of the soleus muscle, increased in vitro growth of myoblasts, and accelerated their differentiation. These processes were accompanied by alterations of GAG contents. These results indicate that the control of TGFβ 1 activity is important to improve regeneration of injured muscle and accelerate myoblast differentiation, in part through changes in GAG composition of muscle cell environment.